Análisis de los insecticidas organofosforados y su mecanismo de acción en los sembríos - Haz Rodríguez, Denise Antonella (2023)
Regarding the development of the case study, the need to analyze organophosphate insecticides in the agricultural sector in Ecuador arises. Regarding the general objective that has been raised in this study, it is based on analyzing organophosphate insecticides and their mechanism of action in crops. It is important to indicate that "organophosphorus" pesticides belong to a category of chemical products widely used in agriculture, being their chemical composition based on phosphate. These compounds play a crucial role by directly affecting the nervous system of insects present in cultivation areas, which classifies them as neurotoxic insecticides due to their mode of action. The execution of this study is justified because it allows us to understand the importance of these chemical products, as well as the mechanism of action they have in terms of agriculture, which is crucial to be able to control the advance of pests. Regarding the methodology of this study, the type of research carried out is based on a bibliographic and documentary study, where descriptions of the characteristics of the phenomenon analyzed are described. Based on the results, they reveal a series of significant findings where it has been confirmed that organophosphorus insecticides exert an action through a process of inhibition of the enzyme "acetylcholinesterase" that affects the nervous system of the insect group. In conclusion, it has been possible to determine the importance of organophosphate insecticides in crops, where the results show that these insecticides can play an important role in protecting crops against pests.